Geographic Drivers of Antimicrobial Use and Resistance in Pigs in Khon Kaen Province, Thailand - Huber, Laura; Hallenberg, Gunilla Ström; Lunha, Kamonwan; Leangapichart, Thongpan; Jiwakanon, Jatesada; Hickman, Rachel A.; Magnusson, Ulf; Sunde, Marianne; Järhult, Josef D.; Van Boeckel, Thomas P. (Frontiers in Veterinary Science, 2021)
In Thailand, pig production has increased considerably in the last decades to meet a growing demand for pork. Antimicrobials are used routinely in intensive pig production to treat infections and increase productivity. However, the use of antimicrobial also contributes to rise of antimicrobial resistance, with potential consequences for animal and human health. Here, we quantified the association between antimicrobial use and resistance rates in extensive and intensive farms, with a focus on geographic proximity between farm and drugstores. Of the 164 enrolled farms, 79% reported using antimicrobials for disease prevention, treatment, or as feed-additive. Antimicrobial resistant E. coli were present in 63% of farms. These drugs included critically important antimicrobials, such as quinolones, and penicillins. Medium-scale farms with intensive animal production practices, showed higher resistance rates than small-scale farms with extensive practices. Farms with drug resistant-Escherichia coli, were located closer to drugstores and a had higher proportion of disease than farms without drug resistant-E. coli. We found no association between the presence of resistance in humans and antimicrobial use in pigs. Our findings call for actions to improve herd health to reduce the need for antimicrobials, and systematic training of veterinarians and drugstore owners on judicious use of antimicrobials in animals to mitigate resistance. Key-words: Escherichia coli, antimicrobial resistance, antimicrobial use, pig, intensive production